2019
DOI: 10.32783/csid-jid.v2i2.66
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Driver Behavior to Hydroplaning in the State of Florida Using Driving Simulation

Abstract: This project used a driving simulator to investigate patterns of drivers' behavior during rainfall events using different geometries. The researchers conducted a literature review of previous transportation studies using driving simulators and selected and analyzed extensive field data on major highway sections throughout Florida. The driving simulator at the University of Central Florida simulated the parameters such as speed and rainfall intensity observed in the field. Based on an analysis, the researcher f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 4 publications
(5 reference statements)
0
1
0
Order By: Relevance
“…A previous study conducted by Florida Department of Transportation (FDOT) indicated that a typical driver is expected to reduce the vehicle speed during a rainfall event ( 2 ). More specifically, the study showed that, while the driving speed during a light rainfall event (i.e., rainfall intensity less than 0.25 in./h) is relatively unaffected, the speed is reduced by 6 mph to 12 mph during a heavy rainfall event (i.e., rainfall intensity greater than 0.25 in./h).…”
Section: Study Backgroundmentioning
confidence: 99%
“…A previous study conducted by Florida Department of Transportation (FDOT) indicated that a typical driver is expected to reduce the vehicle speed during a rainfall event ( 2 ). More specifically, the study showed that, while the driving speed during a light rainfall event (i.e., rainfall intensity less than 0.25 in./h) is relatively unaffected, the speed is reduced by 6 mph to 12 mph during a heavy rainfall event (i.e., rainfall intensity greater than 0.25 in./h).…”
Section: Study Backgroundmentioning
confidence: 99%